Chinese Consumer Engagement with eWOM Websites and Assessing the Credibility of Content for Tourism to European Countries - Chang, H.C. (2017)
Electronic word-of-mouth (eWOM) is regarded as the key source of tourism information search for consumers and thus has become the marketing communication focus for tourism service industry. This research targeted Chinese tourists as the research objectives since Chinese outbound tourism has grown rapidly within these few years. Within the European tourism context, this research explores factors for eWOM engagement and determinants that affect eWOM credibility, and examines within the same context whether credibility affects consumers’ tourism product purchasing decision making. An online survey was conducted to investigate eWOM engagement variables: self-enhancement, social benefit, advice seeking, concern for others, and helping the company; and eWOM credibility evaluation determinants: argument strength and review with photos. Results of eWOM engagement factor analysis shows that self-enhancement is the prominent factor for Chinese consumers to engage in eWOM. In addition, results also suggest that both argument strength and reviews with photos have positive effects on eWOM credibility evaluation. Moreover, the outcome indicates the higher credibility will positively affect consumers’ purchasing decision making.